1984
DOI: 10.1111/j.1600-0536.1984.tb00343.x
|View full text |Cite
|
Sign up to set email alerts
|

The baboon syndrome: systemically‐induced allergic contact dermatitis*

Abstract: The catchword "baboon syndrome" is used to denote a characteristic distribution pattern of systemic allergic contact dermatitis. Diffuse erythema of the buttocks, upper inner surface of the thighs, and axillae are characteristic features. We describe 3 cases provoked by ampicillin, nickel and mercury. The condition may be overlooked and suspected of being a textile dermatitis or seborrhoeic dermatitis of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0
15

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(180 citation statements)
references
References 3 publications
4
161
0
15
Order By: Relevance
“…Perineal eritemle gelen olgularda perianal bölge muayenesi yapılmalı ve ağrılı defekasyon sorgulanmalıdır 3,9 . Perineal ve/veya inguinal eritem, 1984 yılında tanımlanan nadir görülen nikel, civa ve ilaçlar gibi Tip IV alerjenlere oral maruziyet sonrası oluşan sistemik kutanöz bir reaksiyon olan Baboon Sendromunu (BS) da düşündürmelidir 10 . Genellikle topikal uygulama sonrası oluşan duyarlanma ile etkene tekrar topikal veya sıklıkla sistemik maruziyet sonrası klinik oluşur.…”
Section: Discussionunclassified
“…Perineal eritemle gelen olgularda perianal bölge muayenesi yapılmalı ve ağrılı defekasyon sorgulanmalıdır 3,9 . Perineal ve/veya inguinal eritem, 1984 yılında tanımlanan nadir görülen nikel, civa ve ilaçlar gibi Tip IV alerjenlere oral maruziyet sonrası oluşan sistemik kutanöz bir reaksiyon olan Baboon Sendromunu (BS) da düşündürmelidir 10 . Genellikle topikal uygulama sonrası oluşan duyarlanma ile etkene tekrar topikal veya sıklıkla sistemik maruziyet sonrası klinik oluşur.…”
Section: Discussionunclassified
“…Sensitized individuals generally experience a predictable localized response following coetaneous exposure to nickel, including erythema, vesicle formation, scaling, and pruritus. According to recent studies, females have an about 4-fold higher relative risk of developing allergic contact dermatitis to nickel compared with males [9,10]. A recently published study of a German population showed a positive association between filaggrin mutations, which have been shown to be strongly associated with AD, and contact sensitization to nickel [11].…”
Section: ) Nickel and Scdmentioning
confidence: 99%
“…Another presentation for mercury contact allergy is' baboon syndrome'. This entity was described by Andersen et al in 1984 and is characterized by a systemic contact dermatitis that involves a pruritic and confluent macular and papular light-red eruption localized to the gluteal cleft and major flexures. It can result from contact with various allergens, but mercury is a classic cause.…”
Section: Mercurymentioning
confidence: 99%